Surface Features of Bacillus polymyxa Spores as Revealed by Scanning Electron Microscopy - Murphy, Judith A. (1969)
The surface features of Bacillus polymyxa spores were compared by use of thin sections, carbon replicas, and the scanning electron microscope. Some features of the characteristic ridges, previously reported in ultrathin sections and carbon replicas of spores of this species, were more clearly revealed with the scanning electron microscope. A three-dimensional image is provided because of the greater depth of focus possible with this instrument. End-on views of B. polymyxa spores readily illustrate the polygonal porelike structure present.